ChemInform Abstract: Structure, Stability, and Photoluminescence in the anti‐Perovskites Na3W1‐xMoxO4F (0 ≤ x ≤ 1). Issue 43 (October 2015) - Sullivan, Eirin; Avdeev, Maxim; Blom, Douglas A.; Gahrs, Casey J.; Green, Robert L.; Hamaker, Christopher G.; Vogt, Thomas
Abstract Na3WO4F, Na3MoO4F, and Na3W1‐xMoxO4F (x = 0, 0.25, 0.5, 0.75, 1) are prepared via melting of stoichiometric amounts of Na2WO4 (Na2MoO4) and NaF in air (635 °C, 20 h).